Association between ethical leadership, ethical climate and organizational citizenship behavior from nurses' perspective: a descriptive correlational study - Soudabeh Aloustani; Foroozan Atashzadeh-Shoorideh; Mansoureh Zagheri-Tafreshi; Maliheh Nasiri; Maasoumeh Barkhordari-Sharifabad; Victoria Skerrett (BMC, 2020)
Abstract Background Ethical leadership plays an important role in improving the organizational climate and may be have an effect on citizenship behavior. Despite the growing emphasis on ethics in organizations, little attention to has been given this issue. The purpose of this study was to identify ethical leadership, an ethical climate, and their relationship with organizational citizenship behavior from nurses' perspective. Methods In this descriptive correlational study, 250 nurses in twelve teaching hospitals in Tehran were selected by multistage sampling during 2016-2017. The data were collected using Ethical Leadership Questionnaire, Hospital Ethical Climate Survey, and Organizational Citizenship Behavior Scale. Results The findings showed a significant correlation between ethical leadership in managers, organizational citizenship behavior (P = 0.04, r = 0.09) and an ethical climate (P < 0.001, r = 0.65). There was a significant correlation between an ethical climate and nurses' organizational citizenship behavior (P < 0.001, r = 0.61). The regression analysis showed that ethical leadership and an ethical climate is a predictor of organizational citizenship behavior and confirms the relationship between the variables. Conclusion Applying an ethical leadership style and creating the necessary conditions for a proper ethical climate in hospitals lead to increased organizational citizenship behavior by staff. To achieve organizational goals, nurse managers can use these concepts to enhance nurses' satisfaction and improve their performance.